Evaluating the Non-Linear Behaviour of a Timber-Steel Moment Resisting Connections - Hossein Pour, Morteza (Université d'Ottawa / University of Ottawa, 2023)
Timber moment resisting connections have gained considerable interest in structural design due to the numerous advantages offered by timber as a lightweight, renewable, sustainable, and aesthetically pleasing material. This research focuses on investigating the feasibility and potential benefits of hybrid timber-steel moment connections in enhancing the seismic performance and ductility of timber structures. The objective is to evaluate the response modification factors of the hybrid timbersteel moment-resisting frames to see if this type of moment connection has the ability to perform like steel moment-resisting frames in lateral loadings. The process by which the studied frames were designed was focused on preventing damage to timber elements by inducing inelastic deformations exclusively in the steel beams, while the remaining parts of the frame retain their elasticity. Nonlinear static analysis is employed to evaluate the force modification factors and nonlinear behavior of the selected structures. In this study, a total of 18 frames with different span lengths, numbers of stories, and seismicity levels were analyzed to comprehensively investigate their seismic performance. The frames were designed to represent a range of practical configurations commonly found in timber structures. The span lengths of 4, 6, and 8 meters were considered. The number of stories were 2, 4, and 6, and the frames were located in Montreal, QC, and Vancouver, BC, which are known for having varying seismic conditions. By considering a diverse set of frames, this study tried to provide a comprehensive understanding of the behavior and performance of different timber frame structures under seismic loading, taking into account the effects of span length, number of stories, and regional seismic conditions. The results of the analysis offer a preliminary understanding of the seismic performance and potential advantages of steel-timber moment connection frames. However, it should be noted that further research is needed to conduct full-scale experimental tests to validate the proposed connections and gather more accurate data. The findings from this study have the potential to contribute to the development of new seismic provisions for moment connection timber frame systems, advancing the field of timber structural design and offering potential design schemes that increase ductility and performance in timber moment resisting connections.
Keywords: Timber-steel connections; Moment resisting connections; Nonlinear behaviour